Soil microbial community shifts explain habitat heterogeneity in two Haloxylon species from a nutrient perspective. Issue 1 (3rd January 2023) - Li, Chenhua; Li, Yan; Tang, Lisong; Ikenaga, Makoto; Liu, Ran; Xu, Guiqing
Abstract: Haloxylon ammodendron and Haloxylon persicum (as sister taxa) are dominant shrubs in the Gurbantunggut Desert. The former grows in inter‐dune lowlands while the latter in sand dunes. However, little information is available regarding the possible role of soil microorganisms in the habitat heterogeneity in the two Haloxylon species from a nutrient perspective. Rhizosphere is the interface of plant–microbe–soil interactions and fertile islands usually occur around the roots of desert shrubs. Given this, we applied quantitative real‐time PCR combined with MiSeq amplicon sequencing to compare their rhizosphere effects on microbial abundance and community structures at three soil depths (0–20, 20–40, and 40–60 cm). The rhizosphere effects on microbial activity (respiration) and soil properties had also been estimated. The rhizospheres of both shrubs exerted significant positive effects on microbial activity and abundance (e.g., eukarya, bacteria, and nitrogen‐fixing microbes). The rhizosphere effect of H. ammodendron on microbial activity and abundance of bacteria and nitrogen‐fixing microbes was greater than that of H. persicum . However, the fertile island effect of H. ammodendron was weaker than that of H. persicum . Moreover, there existed distinct differences in microbial community structure between the two rhizosphere soils. Soil available nitrogen, especially nitrate nitrogen, was shown to be a driver of microbial community differentiation among rhizosphere and non‐rhizosphere soils in the desert. In general, the rhizosphere of H. ammodendron recruited more copiotrophs (e.g., Firmicutes, Bacteroidetes, and Proteobacteria), nitrogen‐fixing microbes and ammonia‐oxidizing bacteria, and with stronger microbial activities. This helps it maintain a competitive advantage in relatively nutrient‐rich lowlands. Haloxylon persicum relied more on fungi, actinomycetes, archaea (including ammonia‐oxidizing archaea), and eukarya, with higher nutrient use efficiency, which help it adapt to the harsher dune crests. This study provides insights into the microbial mechanisms of habitat heterogeneity in two Haloxylon species in the poor desert soil. Abstract : Haloxylon ammodendron and Haloxylon persicum (as sister taxa) grow in adjacent and distinct habitats in the Gurbantonggut Desert, with the former growing on interdunes and the latter on sand dunes. The rhizosphere of H. ammodendron recruited more copiotrophs (e.g., Proteobacteria, Bacteroidetes, N‐fixing microbes, and AOB), and with stronger microbial activities, which helps it maintain a competitive advantage in relatively nutrient‐rich lowlands. H. persicum relied more on eukarya, fungi, actinomycetes, and archaea (including AOA), with higher nutrient use efficiency, which help it adapt to the poorer sand dunes.